Strategi Pengembangan Pariwisata Berkelanjutan di Hutan Lindung Desa Sesaot Kecamatan Narmada Kabupaten Lombok Barat - Muhammad Shofiyan Al Asy’ary; Sri Sundari (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2022)
There are still problems of Sustainable tourism development in Sesaot Forest. They are: (1) low human resources, (2) lack of infrastructure and facilities in the form of the accessibility road to the location; (3) and illegal logging. This research aims to identify the strategies of the Department of Tourism of West Lombok for the sustainable development, in Sesaot Protected Forest, West Nusa Tenggara. The method used in this research is descriptive qualitative approach. Data were collected through interviews, documentation and observation. Data analysis technique used is the SWOT (Strenght, Weakness, Opportunity, and Threats). As the result, sustainable tourism development in Sesaot Forest are affected by six dimensions, they are: (1) selecting the basic problem, (2) setting basic goals and strategic objective, (3) formulating an action plans, (4) developing empowerment plans, (5) considering the excellence, (6) considering the sustainability. However, dimension of setting basic goals and strategic objective and formulating an action plans do not work well. Therefore, Department of Tourism depute local communities and make tour packages which are conducted by local communities themselves. For better development, West Lombok Government also have to compile the regulation about Sustainable Tourism.